Effects of Murraya koenigii leaves on glucose level, kidney and islets of langerhans in streptozocin induced diabetes in rats - Al-Ani, Imad Matloub Dally; Imam Santosa , Rahajoe; Yankuzo, Muhammad H.; Saxena, Anil Kumar (2012)
In the present study, in addition to 30 days antihyperglycaemic effect of curry leaves of Murraya koenigii "MK" aqueous leaf extract, we also examined its possible effects on the Islets of Langerhans and nephro-protective potential in Streptozotocin (STZ) induced diabetic rats. Male Sprague Dawley rats received a single dose of STZ (70 mg/kg) intraperitoneally to induce experimental diabetes. Rats were randomized into five groups (n=6) of normal control, diabetic control (non-treated), and diabetic treated with MK aqueous leaf extract. The fresh leaves of MK was extracted with distilled water and freeze-dried to powder. Blood glucose levels and body weight were monitored gravimetrically. The animals were killed on the 30th day, kidney and the pancreatic tissues were harvested, and the tissue specimens were fixed in 10% formal saline for 48hrs, and processed for histological studies. Diabetic rats treated with aqueous extract showed significant (p < 0.001) improvement in blood glucose levels and body weight gain. The MK extract also showed improvements in tissue injury induced by STZ. Thus, these findings highlighted the beneficial effects of curry leaf aqueous extract against STZ induced cellular damage and may exert anti-hyperglycemic action and regeneration of kidney and islet cell induced in diabetic rats.